Symptomatology of posttraumatic stress and burnout associated with aggressions suffered by primary care health professionals. A transversal study - Gascon-Santos, Santiago; Oliván-Blázquez, Bárbara; Chambel, Maria José; Sebastián, Lucía; Alacreu-Crespo, Adrián; Pérez-Montesinos, Yago; Paúl, Pilar; Fueyo-Díaz, Ricardo (Frontiers in Psychology, 2024)
Objective: To know the incidence of aggressions in Primary Care, and to determine the psychological symptoms that may accompany these experiences. A transversal study was carried out in North-Eastern Spain, in 2022.: 207 participants (60.9% women, mean age 48.8 years), primary care professionals (nurses and doctors), responded to Questionnaire of Sociodemographic and Occupational variables, List of Aggressions, General Health Questionnaire, Posttraumatic Stress Disorder Checklist, and Maslach Burnout Inventory.Results: 57.49% had suffered aggressions in the last year (44.4% threats, 55.1% insults and 18.4% physical aggressions). They showed more psychological symptoms than those who had not been assaulted: re-experiencing, avoidance, distancing, emotional or cognitive disturbances and hypervigilance, as well as to emotional exhaustion, depersonalization and low personal realization.Although no statistically significant differences were found in terms of the number of victims with respect to gender, men showed more symptoms of trauma.The data show the increase of violent episodes in Primary Care. Although the attacks perpetrated in this sector do not usually present the magnitude required for the diagnosis of Post-Traumatic Stress, many of its symptoms were manifested in those who had suffered violence. Likewise, a relationship was found between aggression and burnout.The need to have post-incident protocols is evident, raising awareness among professionals about the importance of reporting episodes, as well as designing and implementing prevention plans. The damage generated by these behaviors does not only affect nurses and doctors, but, indirectly, all users of the health system.